Berezin symbols and Borel summability. Issue 3 (28th April 2017) - Garayev, M.T.; Gürdal, M.; Yamancı, U.
Abstract: We prove in terms of so-called Berezin symbols some theorems for Borel summability method for sequences and series of complex numbers. Namely, we characterize the Borel convergent sequences and series; prove regularity of Borel summability method, and prove a new Tauberian type theorem for Borel summability.